Ternary Substituted Vanadium Phosphate Electrode Materials

The ternary substituted vanadium phosphate electrode material addresses the challenges of sodium ion batteries by enhancing electrochemical performance and reducing vanadium content, resulting in improved rate capabilities and cyclability.

JP7648676B2Active Publication Date: 2025-03-18HINDUSTAN PETROLEUM CORP LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023080788
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-19
Filing Date
2023-05-16
Publication Date
2025-03-18
Estimated Expiration
2043-05-16

AI Technical Summary

Technical Problem

Existing sodium ion battery technologies face challenges in achieving high voltage, high capacity, and cycle stability due to the large size of sodium ions and the high cost of vanadium, which limits the practical use of vanadium-based electrode materials.

Method used

The development of a ternary substituted vanadium phosphate electrode active material with the general formula A_y B_(3+x-y) V_(2-x) C_x (PO_4)_(3-(z/3)) D_z, where A is Li or K, B is selected from Li, Na, K, C is a transition metal or alkaline earth metal, and D is a halogen, which improves electrochemical properties and reduces vanadium content.

Benefits of technology

The ternary substituted vanadium phosphate electrode material exhibits improved rate capabilities, cyclability, and high-speed charging and discharging characteristics, making it suitable for commercialization while maintaining acceptable charge/discharge cycle characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648676000002
    Figure 0007648676000002
  • Figure 0007648676000003
    Figure 0007648676000003
  • Figure 0007648676000004
    Figure 0007648676000004
Patent Text Reader

Abstract

To provide: an electrode active material realizing improved discharge capacity and charge-discharge cycle characteristics; a method for producing the electrode active material; an electrode material for a metal ion battery; a method for producing the electrode material for a metal ion battery; and a metal ion battery.SOLUTION: The invention provides a ternary substituted vanadium phosphate electrode active material and a battery comprising the same, where the electrode active material has the general formula (1), AyB(3+x-y)V(2-x)Cx(PO4)(3-(z / 3))Dz, where: A is Li or K; B is selected from Li, Na and K; C is a transition metal, a post-transition metal, or an alkaline earth metal; D is selected from F, Cl, Br and I; V is vanadium; PO4 is phosphate; x is a real number from 0.001 to 1.0; y is a real number from 0.001 to 0.5; and z is a real number from 0.001 to 0.5; with the proviso that A and B are not simultaneously Li or simultaneously K.SELECTED DRAWING: Figure 4(a)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to electrode materials, more particularly to ternary substituted vanadium phosphate electrode active materials and batteries containing the same. [Background technology]

[0002] Typically, in secondary batteries, commonly used for electrochemical energy conversion and storage, two electrodes and an electrolyte are commonly used, and electrochemical reactions proceed at both electrodes with more or less change in the composition of the electrolyte. During the electrochemical reactions in the cell, components of the electrolyte solution are often consumed and new components are generated. Changes related to the nature of the electrolyte are most often undesirable, since they can cause, for example, a decrease in ionic conductivity and an increase in the internal resistance of the device. A certain minimum amount of electrolyte is essential for sustained cell performance.

[0003] Representative examples of metal-ion batteries reported in various studies include sodium-ion batteries, lithium-ion batteries, potassium-ion batteries, magnesium-ion batteries, calcium-ion batteries, and fluorine-ion batteries. In recent years, research on sodium-based secondary batteries using sodium instead of lithium has been attracting renewed attention. Sodium reserves are abundant, and if secondary batteries using sodium instead of lithium can be manufactured, it may be possible to manufacture secondary batteries at low cost. In addition, unlike lithium-ion batteries, which basically use nickel or cobalt as the positive electrode material, sodium-ion batteries do not require the use of expensive nickel or cobalt as the positive electrode material. However, sodium secondary batteries have different physical properties from existing lithium secondary batteries. Because renewable energy sources are intermittent, energy storage systems that can store energy whenever it is available are very important. For this reason, energy storage systems need to have a large storage capacity and be relatively inexpensive.

[0004] In sodium-ion batteries, the electrode material is a key factor that affects the performance and cost of the battery compared to other materials. The electrode material currently being studied, a novel NASICON-type sodium vanadium phosphate material, has excellent stability and a relatively high specific capacity. However, there are limitations in the electrochemical properties of sodium vanadium phosphate positive electrode materials synthesized by chemical synthesis, especially the conductivity and high-rate long-cycle performance. In addition, in this context, materials such as layered transition metal oxides, tunnel-type oxide materials, sulfates, polyanion compounds, phosphates, pyrophosphates, and Prussian blue analogues have also been reported. Polyanion compounds, especially phosphates with PO bonds, are known to be stronger and have a very robust structure that does not undergo structural changes during charging and discharging. Therefore, various studies are being conducted to optimize the phosphate electrode material itself not only to improve its properties but also to enable its use in various metal-ion batteries.

[0005] For example, Chinese Patent Publication No. 114256446 discloses a polyanion-type positive electrode material. The electrode material disclosed therein has the general formula: A3V 2-m B m (PO4) 3-n D n / C. This electrode material is disclosed to be applied as a positive electrode material in metal ion batteries. In addition, China Patent Publication No. 114156470 discloses a sodium-rich phase vanadium zinc phosphate material. This material has the general formula Na 3+x V 2-x Zinc x It is expressed as (PO4)3 / C(NVZP) and is used as the positive electrode (or cathode) in sodium-ion batteries.

[0006] China Patent Publication No. 114538400 relates to a multi-cation substituted phosphate electrode material. The element-doped sodium vanadium phosphate electrode material disclosed therein has a higher proportion of sodium than other metals.

[0007] China Patent Publication No. 114156470 discloses a sodium-rich phase vanadium zinc sodium phosphate material. In particular, the preparation method is disclosed in which a vanadium source, a sodium source, a phosphorus source and a zinc source are mixed in a certain molar ratio and reacted under magnetic stirring. The electrode material is used in sodium-ion batteries.

[0008] Despite the above-mentioned state of the art in electrode materials, the development of sodium-ion battery technology is still immature because the inherent size of Na (1.02 Å) is larger than that of Li (0.72 Å). Although all components of a battery (cathode, anode, current collector, electrolyte, separator, etc.) contribute to the overall battery performance, the cathode remains critical and highly desirable for imparting high voltage, high capacity, and cycle stability to the entire battery.

[0009] In summary, there are a wealth of polyanion-based materials with high voltage, energy density, power density, and excellent cycle stability, such as Na3V2(PO4)2F3(NVPF), Na3V2O2(PO4)F(NVOPF), and Na3V2(PO4)3(NVP). However, these materials contain a large amount of vanadium, and the high price of vanadium is a major obstacle to their practical use. The price of vanadium is comparable to that of nickel. Therefore, it is essential to reduce the vanadium content for commercialization. Furthermore, it is also important that the electrochemical properties of the electrode material are not impaired thereby. Therefore, there is a constant demand to provide suitable electrode materials that not only reduce the vanadium content but also have improved discharge capacity and are scalable to commercial levels while providing acceptable or improved charge-discharge cycle properties.

[0010] It is therefore an object of the present invention to provide an electrode material for metal-ion batteries that is effective in alleviating one or more of the problems in the prior art. Summary of the Invention

[0011] It has surprisingly been found that the above objectives are achieved by providing the electrode active materials disclosed herein.

[0012] The present invention provides an electrode active material of the following general formula 1: A y B (3+x-y) V (2-x) C x (PO4) (3-(z / 3)) D z (1) Where: A is Li or K; B is selected from Li, Na, and K; C is a transition metal, a post-transition metal, or an alkaline earth metal; D is selected from F, Cl, Br, I; V is vanadium; PO4 is phosphate, x is a real number between 0.001 and 1.0, y is a real number between 0.001 and 0.5, z is a real number between 0.001 and 0.5. However, A and B are not both Li or both K.

[0013] In one embodiment, C is selected from Mg, Ti, Cr, Al, Fe, Bi, Sr, Mn, Co, Ni, Cu, Zn, Sc, Tc, Pd, Mo, Sn, and W.

[0014] In another embodiment, x is between 0.01 and 0.5, y is between 0.01 and 0.1, and z is between 0.01 and 0.1.

[0015] In yet other embodiments, the electrode active material is coated with one or more selected from the group consisting of conductive carbon, precious metals, and metals.

[0016] In another aspect, the present invention relates to a method for producing an electrode active material, the method comprising the steps of obtaining a solution containing precursors of A, B, C, D, V, and PO4, where A, B, C, D, V, and PO4 are as defined above, mixing the solution at 60°C to 120°C to obtain a gel, drying the gel by freeze-drying, and calcining the dried gel to obtain an electrode active material.

[0017] In one embodiment, the drying step is carried out at -55°C to -30°C.

[0018] In other embodiments, the solution further comprises a carbon source selected from citric acid, glucose, sucrose, fructose, ascorbic acid, lignin, polysaccharides, hydrolyzed starch, dextrin, and molasses. The method further comprises grinding the dried gel prior to calcining the dried gel.

[0019] In another embodiment, the precursor of A is selected from the group consisting of lithium hydroxide, lithium carbonate, lithium perchlorate, potassium hydroxide, potassium carbonate, potassium perchlorate, potassium chloride, potassium sulfate, and potassium nitrate.

[0020] In another embodiment, the precursor of B is selected from the group consisting of lithium hydroxide, lithium carbonate, lithium perchlorate, sodium carbonate, sodium hydroxide, sodium dihydrogen phosphate, sodium oxalate, sodium citrate, sodium phosphate, disodium hydrogen phosphate, sodium chloride, sodium dodecylbenzenesulfonate, sodium sulfate, sodium nitrate, potassium hydroxide, potassium carbonate, potassium perchlorate, potassium chloride, potassium sulfate, and potassium nitrate.

[0021] In yet another embodiment, the precursor of C is one or more hydroxides or nitrates or sulfates selected from the group consisting of Mg, Ti, Cr, Al, Fe, Bi, Sr, Mn, Co, Ni, Cu, Zn, Sc, Tc, Pd, Mo, Sn, and W.

[0022] In yet other embodiments, the precursor of V is selected from the group consisting of ammonium metavanadate, vanadium pentoxide, vanadyl acetylacetonate, vanadyl sulfate, vanadium dioxide, and vanadium trioxide.

[0023] In other embodiments, the precursor of PO4 is selected from the group consisting of monoammonium phosphate, diammonium phosphate, phosphoric acid, monosodium phosphate, ammonium phosphate, disodium phosphate, and ammonium dihydrogen phosphate.

[0024] In other embodiments, the precursor of D is selected from the group consisting of potassium fluoride, sodium fluoride, ammonium fluoride, lithium fluoride, potassium chloride, sodium chloride, ammonium chloride, magnesium chloride, lithium chloride, potassium bromide, sodium bromide, ammonium bromide, lithium bromide, potassium iodide, sodium iodide, ammonium iodide, and lithium iodide.

[0025] In yet another aspect, the present invention relates to an electrode material for a metal ion battery comprising the above-mentioned electrode active material.

[0026] In one embodiment, the electrode material further comprises a binder selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, polyacrylic acid, alginic acid, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butadiene rubber, and fluorinated rubber.

[0027] In other embodiments, the electrode material further comprises a conductive material selected from carbon black, acetylene black, ketjen black, reduced graphene oxide, and carbon nanotubes.

[0028] In another aspect, the present invention relates to a method for producing an electrode material. The method includes obtaining a slurry containing an electrode active material, a binder, and one or more selected from the group consisting of conductive carbon, a noble metal, and a metal. Based on the total weight of the slurry, the amount of the electrode active material is 50% to 90% by weight, and the amount of the binder is 1% to 20% by weight. The method further includes coating the slurry on a conductive material and then drying to obtain an electrode material.

[0029] In yet another aspect, the present invention relates to a metal-ion battery comprising the above-described electrode material. [Brief description of the drawings]

[0030] [Figure 1(a)] FIG. 1(a) is a low magnification scanning electron microscope (SEM) image of a KNVZPF material according to one embodiment of the present invention. [Figure 1(b)] FIG. 1(b) is a high magnification scanning electron microscope (SEM) image of a KNVZPF material according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an X-ray diffraction (XRD) image of a KNVZPF material, a NVZPF material, a NVZP material, and an NVP material according to one embodiment of the present invention. [Figure 3(a)] FIG. 3(a) shows the charge and discharge characteristics of a KNVZPF material according to one embodiment of the present invention at a current density of 0.1 C. [Figure 3(b)] FIG. 3(b) shows the charge and discharge characteristics of a KNVZPF material according to another embodiment of the present invention at a current density of 0.1 C. [Figure 3(c)] FIG. 3(c) shows the charge and discharge characteristics of a KNVZPF material according to yet another embodiment of the present invention at a current density of 0.1 C. [Figure 4(a)] FIG. 4(a) shows the rate performance of a KNVZPF material according to one embodiment of the present invention at various current densities (0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 5C, 10C, 20C, 30C, 40C, and 50C). [Figure 4(b)]FIG. 4(b) shows the rate performance of a KNVZPF material according to one embodiment of the present invention at various current densities (0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 5C, 10C, 20C, 30C, 40C, and 50C). [Figure 4(c)] FIG. 4(c) shows the rate performance of a KNVZPF material according to one embodiment of the present invention at various current densities (0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 5C, 10C, 20C, 30C, 40C, and 50C). [Diagram 5] FIG. 5 shows the rate and cycle performance at 10C rate of the KNVZPF material according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Before the present invention is described, it is to be understood that the scope of this invention will be limited only by the claims and that the terms used herein are not intended to be limiting.

[0032] As used herein, the terms "comprising," "comprises," and "comprised of" are synonymous with "including," "includes," or "containing," "contains," and are used in an inclusive or open sense and do not exclude additional components, elements, or method steps. As used herein, the terms "comprising," "comprises," and "comprised of" should be understood to include the terms "consisting of," "consists," and "consists of."

[0033] Furthermore, the terms "first", "second", "third", or "(a)", "(b)", "(c)", "(d)", etc. in this specification and claims are used to distinguish between similar elements and not necessarily to describe an order or chronology. Terms used in this manner are interchangeable under appropriate circumstances, and the embodiments of the invention described herein can be practiced in other orders than those described or illustrated herein. When the terms "first", "second", "third", or "(A)", "(B)", "(C)", or "(a)", "(b)", "(c)", "(d)", "I", "ii", etc. refer to steps of a method, use, or assay, there is no consistency of time or interval of time between the steps. That is, as described herein, unless otherwise indicated in this application, steps may be performed simultaneously or there may be intervals of seconds, minutes, hours, days, weeks, months or years between such steps.

[0034] In the following text, the different aspects of the invention are defined in more detail. Each aspect can be combined with any other aspect, unless it is clearly indicated to the contrary. In particular, any feature indicated as being preferred or advantageous can be combined with any other feature or function indicated as being preferred or advantageous.

[0035] References throughout this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment of the present invention. Thus, the phrases "in one embodiment" or "in an embodiment" appearing in various places throughout this specification do not necessarily all refer to the same embodiment, although they may. Moreover, as will be apparent to one of ordinary skill in the art from this disclosure, particular features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. Furthermore, some embodiments described herein include some features but not other features included in other embodiments. However, as will be understood by one of ordinary skill in the art, combinations of features of different embodiments are within the scope of the present invention and are meant to form different embodiments. For example, in the claims, any of the claimed embodiments may be used in any combination.

[0036] Furthermore, ranges defined throughout this specification are inclusive of the extreme values, i.e., 1 to 10 includes both 1 and 10. For the avoidance of doubt, Applicant reserves the right to any equivalents available under applicable law.

[0037] As used herein, the terms "sodium salt" and "sodiation" may refer to the process of adding sodium to an electrode active material.

[0038] As used herein, the terms "desodiate" and "desodiation" may refer to the process of removing sodium from an electrode active material.

[0039] As used herein, the terms "charge" and "charging" may refer to the process of providing electrochemical energy to a cell.

[0040] As used herein, the terms "discharge" and "discharging" may refer to a process for removing electrochemical energy from a cell, for example, when using the cell to perform a desired task.

[0041] As used herein, the term "positive electrode" may refer to the electrode (often called the cathode) where electrochemical reduction / sodiation occurs during the discharge process.

[0042] As used herein, the term "negative electrode" may refer to the electrode (often called the anode) where electrochemical oxidation / desodium occurs during the discharge process.

[0043] The present invention is directed to electrode active materials.

[0044] The electrode active material is represented by the general formula 1: A y B (3+x-y) V (2-x) C x (PO4) (3-(z / 3)) D z (1) Where: A is Li or K; B is selected from Li, Na, and K; C is a transition metal, a post-transition metal, or an alkaline earth metal; D is selected from F, Cl, Br, I; V is vanadium; PO4 is phosphate, x is a real number between 0.001 and 1.0, y is a real number between 0.001 and 0.5, z is a real number between 0.001 and 0.5. However, A and B are not both Li or both K.

[0045] In this disclosure, the proviso means that A and B are both selected not to be the same element at the same time, in other words, when A is Li, B is Na or K, and when A is K, B is Li or Na.

[0046] In the state of the art, one of the most widely used materials for metal-ion batteries, especially sodium-ion batteries, is Na3V2(PO4)3, also known as NVP, and Na3V2(PO4)3, also known as NVZP. 3.2 V 1.8 Zinc 0.2 (PO4)3 has been considered. NVP may be referred to interchangeably herein as the "base material."

[0047] It has been observed throughout the present invention that doping NVP with certain elements of the periodic table results in improved electrochemical properties over the base material, where A, B, C, and D each represent an element of the periodic table. By doping the base material with these elements, an electrode active material of general formula 1 is obtained.

[0048] In one embodiment, the substitution A is selected from the periodic table Li or K. Preferably, the substitution A is K or potassium.

[0049] Thus, in one embodiment, the electrode active material is represented by general formula 1a: K y B (3+x-y) V (2-x) C x (PO4) (3-(z / 3)) D z (1a) Where: B is selected from Li or Na; C is a transition metal, a post-transition metal, or an alkaline earth metal; D is selected from F, Cl, Br, and I; V is vanadium; PO4 is phosphate, x is a real number between 0.001 and 1.0, y is a real number between 0.001 and 0.5, z is a real number between 0.001 and 0.5.

[0050] In one embodiment, the substitution B is selected from Li, Na, and K of the periodic table. Preferably, the substitution B is Na or sodium. Thus, the electrode active material where B is Na is referred to as a sodium vanadium phosphate electrode active material. The sodium vanadium phosphate electrode active material may be further substituted with A, C, and D, and thus referred to as a ternary substituted sodium vanadium phosphate electrode active material. This type of ternary substituted material has not been reported in the state of the art, and is therefore unique in itself.

[0051] Thus, in one embodiment, the electrode active material is represented by general formula 1b: A y Na (3+x-y) V (2-x) C x (PO4) (3-(z / 3)) D z (1b) Where: A is Li or K; C is a transition metal, a post-transition metal, or an alkaline earth metal; D is selected from F, Cl, Br, I; V is vanadium; PO4 is phosphate, x is a real number between 0.001 and 1.0, y is a real number between 0.001 and 0.5, z is a real number between 0.001 and 0.5.

[0052] In other embodiments, the substitution C is one of the transition metals, post-transition metals, or alkaline earth metals of the periodic table. Examples of preferred transition metals include Ti, Cr, Fe, Mn, Co, Ni, Cu, Zn, Sc, Tc, Pd, Mo, and W, which are represented in Groups 3 to 12 of the periodic table. Examples of preferred post-transition metals include Al, Sn, and Bi, which are represented in Groups 13 to 15 of the periodic table. Examples of preferred alkaline earth metals include Mg, Sr, and Ca, which are represented in Group 2 of the periodic table.

[0053] In one embodiment, C is selected from Mg, Ti, Cr, Al, Fe, Bi, Sr, Mn, Co, Ni, Cu, Zn, Sc, Tc, Pd, Mo, Sn, and W. Preferably, C is selected from Mn, Co, Ni, Cu, Zn. More preferably, C is Zn or zinc.

[0054] Thus, in one embodiment, the electrode active material is represented by general formula 1c: A y B (3+x-y) V (2-x) Zinc x (PO4) (3-(z / 3)) D z (1c) Where: A is Li or K; B is selected from Li, Na, or K; D is selected from F, Cl, Br, I; V is vanadium; PO4 is phosphate, x is a real number between 0.001 and 1.0, y is a real number between 0.001 and 0.5, z is a real number between 0.001 and 0.5. However, A and B are not both Li or both K.

[0055] In yet other embodiments, the substitution D is selected from the halogens of the periodic table: F, Cl, Br, and I. Preferably, D is F or fluorine.

[0056] Thus, in one embodiment, the electrode active material is represented by general formula 1d: A y B (3+x-y) V (2-x) C x (PO4) (3-(z / 3)) F z (1d) Where: A is Li or K; B is selected from Li, Na, or K; C is a transition metal, post-transition metal, or alkaline earth metal; V is vanadium; PO4 is phosphate, x is a real number between 0.001 and 1.0, y is a real number between 0.001 and 0.5, z is a real number between 0.001 and 0.5. However, A and B are not both Li or both K.

[0057] In other embodiments, x is a real number from 0.005 to 1.0, or a real number from 0.005 to 0.8, or a real number from 0.01 to 0.8. In still other embodiments, x is a real number from 0.01 to 0.5, or a real number from 0.05 to 0.6, or a real number from 0.05 to 0.4. In still other embodiments, x is a real number from 0.1 to 0.4, or a real number from 0.1 to 0.3.

[0058] In still another embodiment, y is a real number from 0.001 to 0.3, or a real number from 0.005 to 0.3, or a real number from 0.01 to 0.3. In another embodiment, y is a real number from 0.01 to 0.1, or a real number from 0.02 to 0.1, or a real number from 0.02 to 0.08. In still another embodiment, y is a real number from 0.03 to 0.08, or a real number from 0.03 to 0.06.

[0059] In still another embodiment, z is a real number from 0.001 to 0.3, or a real number from 0.005 to 0.3, or a real number from 0.01 to 0.3. In another embodiment, z is a real number from 0.01 to 0.1, or a real number from 0.02 to 0.1, or a real number from 0.02 to 0.08. In still another embodiment, z is a real number from 0.04 to 0.07.

[0060] In one embodiment, the electrode active material is coated with one or more selected from the group consisting of conductive carbon, noble metals, and metals. This further improves the electrical conductivity of the material. In one preferred embodiment, the noble metal is selected from Au, Ag, and Pt, and in yet another preferred embodiment, the metal is selected from Cu and Al.

[0061] In order to increase the electrical conductivity without significantly increasing the manufacturing cost and weight, the electrode active material is preferably coated with conductive carbon. Preferred examples of conductive carbon include carbon black, carbon nanotubes, and graphene.

[0062] In another embodiment, the electrode active material is coated with carbon. To this end, a carbon source is added during the synthesis of the material. Suitable examples of carbon sources include citric acid, glucose, sucrose, fructose, ascorbic acid, polysaccharides, hydrolyzed starch, dextrin, and molasses.

[0063] Another aspect of the present invention relates to a method for producing the electrode active material described above. Accordingly, the embodiments described herein with respect to the electrode active material are also applicable to the method of production.

[0064] In one embodiment, a method for producing an electrode active material includes the following steps. (a) obtaining a solution containing precursors of A, B, C, D, V, and PO4 as defined herein; (b) mixing the solution at 60°C to 120°C to obtain a gel; (c) drying the gel by freeze-drying; and (d) Calcining the dried gel to obtain an electrode active material.

[0065] In one embodiment, the precursor of A is selected from the group consisting of lithium hydroxide, lithium carbonate, lithium perchlorate, potassium hydroxide, potassium carbonate, potassium perchlorate, potassium chloride, potassium sulfate, and potassium nitrate. In another embodiment, the precursor of A is selected from the group consisting of lithium carbonate, lithium perchlorate, potassium hydroxide, potassium carbonate, and potassium perchlorate. In yet another embodiment, the precursor of A is selected from the group consisting of potassium hydroxide, potassium carbonate, and potassium perchlorate. In a further embodiment, the precursor of A is potassium hydroxide.

[0066] In one embodiment, the precursor of B is selected from the group consisting of lithium hydroxide, lithium carbonate, lithium perchlorate, sodium carbonate, sodium hydroxide, sodium dihydrogen phosphate, sodium oxalate, sodium citrate, sodium phosphate, disodium hydrogen phosphate, sodium chloride, sodium dodecylbenzenesulfonate, sodium sulfate, sodium nitrate, potassium hydroxide, potassium carbonate, potassium perchlorate, potassium chloride, potassium sulfate, and potassium nitrate. In another embodiment, the precursor of B is selected from the group consisting of lithium hydroxide, lithium carbonate, sodium dodecylbenzenesulfonate, sodium sulfate, sodium nitrate, potassium hydroxide, potassium carbonate, potassium perchlorate, potassium chloride, potassium sulfate, and potassium nitrate. In yet another embodiment, the precursor of B is selected from the group consisting of sodium dodecylbenzenesulfonate, sodium sulfate, and sodium nitrate. In a further embodiment, the precursor of B is sodium nitrate.

[0067] In other embodiments, the precursor of C is one or more hydroxides or nitrates or sulfates selected from the group consisting of Mg, Ti, Cr, Al, Fe, Bi, Sr, Mn, Co, Ni, Cu, Zn, Sc, Tc, Pd, Mo, Sn, and W. In yet other embodiments, the precursor of C is one or more nitrates selected from the group consisting of Mg, Ti, Cr, Al, Fe, Bi, Sr, Mn, Co, Ni, Cu, Zn, Sc, Tc, Pd, Mo, Sn, and W. Preferably, the precursor of C is zinc nitrate.

[0068] In another embodiment, the precursor of V or vanadium is selected from the group consisting of ammonium metavanadate, vanadium pentoxide, vanadyl acetylacetonate, vanadyl sulfate, vanadium dioxide, and vanadium trioxide. Preferably, the precursor of V is ammonium metavanadate.

[0069] In yet another embodiment, the PO4 or phosphate precursor is selected from the group consisting of monoammonium phosphate, diammonium phosphate, phosphoric acid, monosodium phosphate, ammonium phosphate, disodium phosphate, and ammonium dihydrogen phosphate. Preferably, the PO4 precursor is ammonium dihydrogen phosphate.

[0070] In a further embodiment, the precursor of D is selected from the group consisting of potassium fluoride, sodium fluoride, ammonium fluoride, lithium fluoride, potassium chloride, sodium chloride, ammonium chloride, magnesium chloride, lithium chloride, potassium bromide, sodium bromide, ammonium bromide, lithium bromide, potassium iodide, sodium iodide, ammonium iodide, and lithium iodide. In another embodiment, the precursor of D is selected from the group consisting of potassium fluoride, sodium fluoride, ammonium fluoride, lithium fluoride, potassium chloride, sodium chloride, ammonium bromide, lithium bromide, and lithium iodide. Preferably, the precursor of D is ammonium fluoride.

[0071] Thus, in one embodiment, a method for making an electrode active material comprises the following steps. (a) obtaining a solution containing potassium hydroxide, sodium nitrate, zinc nitrate, ammonium metavanadate, ammonium dihydrogen phosphate, and ammonium fluoride; (b) mixing the solution at 60°C to 120°C to obtain a gel; (c) drying the gel by freeze-drying; and (d) Calcining the dried gel to obtain an electrode active material.

[0072] The appropriate amounts of the precursors A, B, C, D, V, and PO4 can be appropriately selected to obtain the compound of general formula 1. In one embodiment, the precursor of A is 0.005% by weight to 5% by weight based on the total weight of the solution.

[0073] In another embodiment, the precursor of B is 1% to 30% by weight, based on the total weight of the solution.

[0074] In yet another embodiment, the precursor of C is 0.1 wt % to 10 wt %, based on the total weight of the solution.

[0075] In yet another embodiment, the V precursor is 1.0% to 20% by weight based on the total weight of the solution.

[0076] In another embodiment, the PO4 precursor is between 5% and 30% by weight based on the total weight of the solution.

[0077] In yet another embodiment, the precursor of D is 0.005% to 5% by weight, based on the total weight of the solution.

[0078] In another embodiment, the solution further comprises a carbon source. The carbon source reduces vanadium ions in the solution. After calcination, the carbon source in the solution is converted to carbon with a uniform thickness on the surface of the electrode active material. This carbon coating improves the electrical conductivity of the material. Preferred examples of carbon sources include citric acid, glucose, sucrose, fructose, ascorbic acid, lignin, polysaccharides, hydrolyzed starch, dextrin, and molasses. Preferably, the carbon source is citric acid.

[0079] The preferred amount of carbon source is known to those skilled in the art, however, in one embodiment, the carbon source is added at 10% to 50% by weight based on the total weight of the solution.

[0080] Thus, in one embodiment, a method for making an electrode active material comprises the following steps. (a) obtaining a solution comprising each of the A, B, C, D, V and PO4 precursors as defined herein and a carbon source; (b) mixing the solution at 60°C to 120°C to obtain a gel; (c) drying the gel by freeze-drying; and (d) Calcining the dried gel to obtain an electrode active material.

[0081] The method is based on sol-gel technology, and the above solutions are mixed at 60° C. to 120° C. to obtain a gel. In one embodiment, the temperature range is 60° C. to 110° C., 60° C. to 100° C., or 60° C. to 90° C. In other embodiments, the temperature is maintained for 1 hour to 12 hours, 2 hours to 10 hours, or 3 hours to 8 hours.

[0082] Suitable mixing means herein are known to those skilled in the art. For example, a stirrer can be used to mix the solution. In addition, suitable solvents, surfactants and other additives commonly used in the preparation of electrode materials are also known to those skilled in the art and can be used in the present invention. Therefore, the present invention is not limited thereto.

[0083] Once the gel is obtained, it is freeze-dried. The temperature suitable for drying is −55° C. to −30° C. The freeze-dried gel is then finely ground and calcined to obtain the electrode active material.

[0084] Calcination typically involves heating the fine powder under an inert atmosphere, such as nitrogen, helium, argon, or mixtures thereof. Suitable temperature ranges for calcination are 300° C. to 1000° C., 300° C. to 950° C., or 300° C. to 900° C., and calcination times are 2 hours to 12 hours, 2 hours to 10 hours, or 4 hours to 10 hours.

[0085] Another aspect of the present invention relates to an electrode material for a metal-ion battery comprising the above-mentioned electrode active material. Accordingly, the embodiments described herein with respect to the electrode active material are also applicable to the electrode material for a metal-ion battery.

[0086] In one embodiment, the electrode material includes a binder. In the present disclosure, the binder serves to promote adhesion between the electrode active materials and improve the bonding of the electrode active materials to the current collector. Suitable binders are selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, polyacrylic acid, alginic acid, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butadiene rubber, and fluorinated rubber.

[0087] In other embodiments, a solvent for the binder is also included. Suitable examples of solvents include, but are not limited to, N-methylpyrrolidone (NMP), acetone, ethanol, and water.

[0088] In yet another embodiment, the electrode material includes a conductive material. The conductive material may be any material commonly used in metal ion batteries. For example, carbon-based materials such as carbon black, acetylene black, ketjen black, reduced graphene oxide, and carbon nanotubes, metal-based materials such as metal powders and metal fibers such as copper, nickel, aluminum, and silver, conductive polymers such as polyphenylene derivatives, or mixtures thereof. The content of the conductive material used can be appropriately adjusted.

[0089] In one embodiment, the conductive material is selected from carbon black, acetylene black, ketjen black, reduced graphene oxide, and carbon nanotubes. Suitable particle sizes of the conductive material are known to those skilled in the art. However, the size should be selected so as not to affect the preparation of the slurry.

[0090] Yet another aspect of the present invention relates to a method for producing the above electrode material. Accordingly, the embodiments described herein with respect to the electrode material and the electrode active material are also applicable to the method for producing the electrode material.

[0091] In one embodiment, a method for producing an electrode material includes the following steps. (a) obtaining a slurry containing an electrode active material, a binder, and one or more selected from the group consisting of conductive carbon, a precious metal, and a metal, The amount of the electrode active material is 50 wt% to 90 wt% and the amount of the binder is 1 wt% to 20 wt% based on the total weight of the slurry; (b) coating the slurry onto a conductive material and then drying to obtain an electrode material.

[0092] Preferably, the slurry includes an electrode active material, a binder, and conductive carbon. The amount of the electrode active material in the slurry is 50% by weight to 90% by weight based on the total weight of the slurry. In one embodiment, the amount of the electrode active material is 60% by weight to 90% by weight, or 70% by weight to 90% by weight.

[0093] The amount of binder in the slurry is from 1% to 20% by weight, based on the total weight of the slurry, hi one embodiment, the amount of binder is from 5% to 20% by weight, or from 5% to 15% by weight.

[0094] Additionally, the slurry also includes one or more selected from the group consisting of conductive carbon, precious metals, and metals. The preferred amount of these materials is 1% to 20% by weight based on the total weight of the slurry. In one embodiment, the amount of these materials is 5% to 20% by weight, or 5% to 15% by weight. In one preferred embodiment, the precious metal is selected from Au, Ag, and Pt. In yet another preferred embodiment, the metal is selected from Cu and Al.

[0095] In the present disclosure, the slurry is applied to the surface of the conductive material. In one embodiment, the slurry coats the surface of the conductive material with a suitable thickness, for example, 300 μm. Those skilled in the art will recognize suitable coating thicknesses, and therefore the present invention is not limited thereby.

[0096] In another embodiment, the drying step is carried out at a temperature between 60°C and 130°C.

[0097] Yet another aspect of the invention relates to a metal-ion battery comprising the above-described electrode material and an electrolyte, and therefore the embodiments described herein with respect to the electrode material are also applicable here.

[0098] The electrode material of the present invention can be used in any metal ion battery with typical components such as, but not limited to, current collectors, electrolytes and separators.

[0099] In the present invention, the current collector is not particularly limited as long as it has conductivity without undergoing chemical changes in the battery. The current collector is, for example, aluminum, nickel, titanium, baked carbon, copper, stainless steel, etc., and may be surface-treated with carbon, nickel, titanium, silver, etc. as necessary. Alternatively, the current collector may be an aluminum-cadmium alloy. In addition, in order to increase the bonding force to the surface of the positive electrode active material, fine irregularities may be formed on the surface of the current collector, and the current collector can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0100] In the present disclosure, the electrolyte includes a liquid electrolyte, a gel polymer, a solid electrolyte, or a combination thereof. The liquid electrolyte includes a sodium salt, an organic solvent, or a combination thereof. The gel electrolyte includes an organic solid electrolyte including a polymer compound, an inorganic solid electrolyte, or a combination thereof. The solid electrolyte includes an organic solid electrolyte including a polymer compound, an inorganic solid electrolyte, or a combination thereof.

[0101] In the present disclosure, when the electrolyte is a liquid electrolyte, the electrolyte comprises an electrolyte salt and a solvent. The electrolyte salt used in the present invention comprises one or more selected from the group consisting of sodium-containing hydroxides (e.g., sodium hydroxide (NaOH) and the like), borates (e.g., sodium metaborate (NaBO2), borax (Na2B4O7), boric acid (H3BO3), and the like), phosphates (e.g., trisodium phosphate (Na3PO4), sodium pyrophosphate (Na2HPO4), and the like), chloric acid (e.g., NaClO4, and the like), NaAlCl4, NaAsF6, NaBF4, NaPF6, NaSbF6, NaCF3SO3, NaN(SO2CF3)2, sodium fluoride, sodium sulfate, sodium nitrate, and sodium lignosulfonate.

[0102] In the present disclosure, the solvent can be used without any particular limitation as long as it is a medium through which ions involved in the electrochemical reaction of the battery move. Specifically, the solvent may be an aqueous solvent such as water or alcohol, or a non-aqueous solvent such as an ester solvent, an ether solvent, a ketone solvent, an aromatic hydrocarbon solvent, an alkoxyalkane solvent, or a carbonate solvent. These solvents can be used alone or in combination of two or more.

[0103] Suitable solvents may be selected from the group consisting of trimethyl phosphate (TMP), triethyl phosphate (TEP), methyl ethyl carbonate, methyl propionate, ethyl propionate, ethyl acetate, ethyl methyl carbonate, methyl formate, propylene carbonate, ethylene carbonate, vinylene carbonate, fluoroethylene carbonate, methyl acetate, triethylene glycol dimethyl ether, dimethyl sulfone, dimethyl ether, ethylene sulfite, diethyl carbonate, dimethyl carbonate, propylene oxide, propylene sulfite, ethylene glycol monobutyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propyl acetate, methyl butanone, methyl isobutyl ketone, toluene cyclohexanone, ethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0104] In the present disclosure, the separator is for separating the negative electrode and the positive electrode from each other and for providing a channel for the movement of metal ions, and any known separator can be used. That is, a separator that has a small resistance to the movement of electrolyte ions and has excellent moisture retention of the electrolyte solution can be used. For example, the separator can be selected from glass microfiber, polyester, Teflon (registered trademark), polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and can be in the form of a nonwoven fabric or a woven fabric. For metal ion secondary batteries, it is preferable to mainly use polyolefin-based polymer separators such as polyethylene and polypropylene, but coated separators containing ceramic components or polymer materials can also be used to ensure heat resistance and mechanical strength. If necessary, the separator may have a single-layer structure or a multi-layer structure.

[0105] The electrode material according to the present invention can be assembled with other components to obtain a metal ion secondary battery.

[0106] Advantageously, the present invention provides improved electrode active materials that have better electrochemical performance in terms of rate capability and cyclability than NVP and NVZP. Moreover, the electrode active materials of the present invention have high-rate charge / discharge capability with good cyclability. Furthermore, the present invention provides a method for easily producing the electrode materials using sol-gel technology with minimal processing requirements.

[0107] While the above description discloses various embodiments of the present disclosure, other and further embodiments of the present invention may be devised without departing from the basic scope of the present disclosure. The present invention is not limited to the described embodiments, versions, or examples, which are included to enable one of ordinary skill in the art to make and use the invention in combination with the information and knowledge available to such person.

[0108] Working Example

[0109] The invention is illustrated by the following non-limiting examples.

[0110] Compound: Precursor of A: Potassium hydroxide (KOH) Precursor of B: Sodium nitrate (NaNO3) Precursor of C: Zinc nitrate (Zn(NO3)2) Precursor of V Ammonium metavanadate (NH4VO3) PO4 Precursor Ammonium dihydrogen phosphate (NH4H2PO4) Precursor of D Ammonium fluoride (NH4F) Solvent: N-methyl-2-pyrrolidone (NMP) Surfactant Cetyltrimethylammonium bromide (CTAB) Binder: Polyvinylidene fluoride (PVDF) Carbon source: Citric acid The above were obtained from Sigma Aldrich. Conductive material BET specific surface area 57~67m 2 / g Carbon Black Obtained from Alfa Aesar.

[0111] Appropriate amounts of NH4VO3, KOH, Zn(NO3)2, NaNO3, NH4H2PO4, NH4F, citric acid, and CTAB were added to deionized water until completely dissolved to obtain a solution. The solution was then kept stirring at 80°C for 6 hours. The solution gelled. The gel was then freeze-dried into a fine powder.

[0112] The fine powder was calcined in an argon atmosphere at 350° C. for 5 hours and then at 750° C. for 8 hours to obtain an electrode active material. The amounts of the various components blended are summarized in Table 1 below.

[0113] [Table 1]

[0114] A comparative material (Comparative Example 1) represented by Na3V2(PO4)3 (referred to as NVP) was prepared using the above ingredients. Figure 1(a) and Figure 1(b) are low and high magnification SEM images of the material of the present invention, KNVZPF. The SEM images reveal a porous structure with irregular morphology. The particle size is 3-5 μm.

[0115] FIG. 2 shows the XRD patterns of NVP, NVZP, NVZPF, and the KNVZPF of the present invention. This comparison reflects the rhombohedral crystal structure of NVP, which is consistent with the standard JCPJDS card number 62-0345 with the R3c space group. The XRD pattern of KNVZPF is consistent with the standard NVP, with no secondary phase formation. Therefore, it shows that K, Zn, and F are successfully substituted into the sodium, vanadium, and phosphate sites. Thus, the substitution of K, Zn, and F does not change the crystal structure.

[0116] The electrode active material, conductive material, and binder were mixed in a weight ratio of 80:10:10 to prepare a slurry. The slurry was then applied to the conductive material and calendered at 80°C to obtain an electrode (positive electrode). Several electrode samples with a diameter of 15 mm were then prepared and further tested.

[0117] Glass fiber separators were cut to a diameter of 19 mm. The electrode samples and separators were transferred to an argon-filled glove box. Half cells were fabricated using metallic Na as the counter and reference electrodes. 1M NaClO4 in propylene carbonate with 5% fluoroethylene carbonate or 1M NaClO4 in propylene carbonate with 5% vinylene carbonate was used as the electrolyte.

[0118] Charge / discharge characteristics of sodium ion batteries using KNVZPF materials

[0119] 3(a)-(c) show the charge-discharge characteristics at 0.1C rate of the KNVZPF materials of Examples 1-3. The charge-discharge characteristics are similar to NVP. Furthermore, a flat potential is observed at 3.4 V, which is characteristic of the redox reaction in typical NVP materials. The discharge capacities were 101 mAh / g, 97 mAh / g, and 94 mAh / g for Examples 1-3, respectively.

[0120] Charge and discharge capacities of sodium-ion batteries using KNVZPF materials

[0121] 4(a) to (c) show the rate performance of the KNVZPF of Examples 1 to 3. Each Example shows good rate performance. Example 1 has the largest capacity, about 90 mAh / g at a 5C rate.

[0122] Figure 5 shows the cycling performance of KNVZPF (Example 1) cycled at a very high C-rate of 10 C. The capacity retention after 2000 cycles is 88%.

[0123] From the above, it can be said that the electrode active material and electrode material according to the present invention are superior in electrochemical cycle properties when compared with NVP and / or NVZP materials known in the art, and furthermore, the electrode active material of the present invention is comparable to NVZPF, a binary substituted NVP material.

Claims

1. An electrode active material having the following general formula 1: K y Na (3+xy) V (2-x) C x (PO 4 ) (3-(z / 3)) D z (1) Where: C is selected from Mg, Ti, Cr, Fe, Sr, Mn, Co, Ni, Cu, Zn, Pd, or Sn; D is selected from F, Cl, or Br; V is vanadium; P.O. 4 is a phosphate salt, x is a real number from 0.001 to 1.0; y is a real number between 0.001 and 0.5; z is a real number between 0.001 and 0.

5.

2. 2. The electrode active material according to claim 1, wherein x is 0.01 to 0.

5.

3. 2. The electrode active material according to claim 1, wherein y is 0.01 to 0.

1.

4. The electrode active material according to claim 1, wherein z is 0.01 to 0.

1.

5. 13. A method for producing the electrode active material of claim 1, comprising the steps of: (a) K, Na, C, D, V, and PO as defined in claim 1 4 obtaining a solution containing the precursors of (b) mixing the solution at 60°C to 120°C to obtain a gel; (c) drying the gel by freeze-drying; and (d) Calcining the dried gel to obtain an electrode active material.

6. The method of claim 5, wherein the drying step is carried out at -55°C to -30°C.

7. The method further comprises the step of forming a carbon coating layer on a surface of the electrode active material after calcination with a carbon source in the solution, 7. The method of claim 5 or 6, wherein the solution further comprises a carbon source selected from citric acid, glucose, sucrose, fructose, ascorbic acid, lignin, polysaccharides, hydrolyzed starch, dextrin, and molasses.

8. 7. The method of claim 5 or 6, further comprising the step of crushing the dried gel prior to the step of calcining the dried gel.

9. An electrode material for a metal ion battery, comprising the electrode active material according to claim 1.

10. The electrode material of claim 9 further comprising a binder.

11. 10. The electrode material of claim 9, further comprising a conductive material selected from carbon black, acetylene black, ketjen black, reduced graphene oxide, and carbon nanotubes.

12. A method for producing the electrode material described in claim 9, further comprising the steps of: (a) obtaining a slurry containing the electrode active material of claim 1, a binder, and one or more selected from the group consisting of conductive carbon, a precious metal, and a metal, Based on the total weight of the slurry, the amount of the electrode active material is 50 wt % to 90 wt %, and the amount of the binder is 1 wt % to 20 wt %; (b) coating the slurry onto a conductive material and then drying to obtain an electrode material.

13. A metal ion battery comprising the electrode material of claim 9 and an electrolyte.

Citation Information

Patent Citations

  • Carbon-coated NaxRyM2(PO4)3 material and preparation and application thereof

    CN109841801A

  • Sodium vanadium fluorophosphate electrode coated with metal oxide layer and preparation method thereof

    CN112186135A

  • Pre-alkali metallization sodium vanadium phosphate, preparation method thereof and sodium ion battery

    CN115172742A

  • Modified manganese-based polyanionic sodium ion battery positive electrode material and preparation method and application thereof

    CN115377413A

  • Secondary electrochemical cell

    JP2013030494A